Factors for Hospitalizations and Neurologic Complications in Zika Virus Infection in the Department of Veterans Affairs (VA). (4th October 2017) - Schirmer, Patricia; Wendelboe, Aaron; Lucero-Obusan, Cynthia; Ryono, Russell; Oda, Gina; Winters, Mark; Saavedra, Sonia; Martinez, Mirsonia; Holodniy, Mark
Abstract: Background: Zika virus (ZIKV) is an important flavivirus, but severity of infection is poorly described in adults. We investigated factors associated with hospitalization and neurologic complications as measures of severity. Methods: ZIKV cases from December 1, 2015 to October 31, 2016 were identified from clinical samples tested in VA, state and commercial laboratories, and patients were followed until 3/31/2017. ZIKV positive patients (RT-PCR or screening IgM positive confirmed by a plaque-reduction neutralization test [PRNT] IgM positive for ZIKV alone or including dengue virus) were reviewed for demographic and clinical factors. Logistic regression analysis was performed to evaluate factors associated with 1) hospitalization and 2) neurologic complications in VA ZIKV positive patients. Results: 736 of 1, 538 (48%) patients tested were ZIKV positive; 655 (89%) were male and 683 (93%) were diagnosed at the VA Caribbean Healthcare System (VACHCS). In total, 94 (13%) were hospitalized with 91 (12%) at VACHCS. 19 (3%) patients, all at VACHCS, died from any cause after ZIKV diagnosis. Hospitalization was more likely with increased age, co-morbidities, neurologic symptoms, thrombocytopenia, or preadmission glucocorticoid use, and less likely if rash was present (Table 1). Hospitalization, prior cerebrovascular disease and dementia were associated with neurologic complications. Conclusion: Older Veterans with multiple comorbidities or presenting with neurologic symptoms were more likely to be hospitalized after ZIKV infection, and those with a prior history of cerebrovascular disease and dementia were at increased risk for neurological complications. Disclosures: All authors: No reported disclosures.